2021
DOI: 10.21082/jtidp.v8n2.2021.p67-78
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Kematangan Buah terhadap Kehilangan Hasil dan Mutu Green Bean Kopi Robusta

Abstract: <em>Kepahiang Robusta coffee has received a Geographical Indication (GI) certificate. Maintaining the quality of green coffee bean has been achieved  through the application of proper harvesting technology. This study aimed to evaluate the effect of fruit maturity level when harvested on yield losses due to coffee berry borer (CBB) and the quality of green coffee bean. The research was conducted from December 2019 to August 2020 in Bukit Sari Village, Kabawetan District, Kepahiang Regency, Bengkulu Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
3
1
1
Order By: Relevance
“…Weight loss tends to be slower but lasts longer, compared to red fruit harvested by selection. This is different from previous research on robusta coffee [2]which explained that the yield of coffee beans with the red fruit harvesting technique had a lower yield than the rainbow, this was due to the presence of PBKo pests that mostly attack red fruit. The character of a thickness of the skin and flesh of the fruit, which is harder and thicker, causes Liberica coffee to be classified as resistant to PBKo pests.…”
Section: Effect Of Harvesting Techniques and Drying Methods On Weight...contrasting
confidence: 99%
See 3 more Smart Citations
“…Weight loss tends to be slower but lasts longer, compared to red fruit harvested by selection. This is different from previous research on robusta coffee [2]which explained that the yield of coffee beans with the red fruit harvesting technique had a lower yield than the rainbow, this was due to the presence of PBKo pests that mostly attack red fruit. The character of a thickness of the skin and flesh of the fruit, which is harder and thicker, causes Liberica coffee to be classified as resistant to PBKo pests.…”
Section: Effect Of Harvesting Techniques and Drying Methods On Weight...contrasting
confidence: 99%
“…From the results and discussion can be concluded several things from this study including (1) The results showed that the highest yield was obtained in the harvest of red fruit in all types of Liberica and Excelsa coffee; (2) The decrease in water content and loss of weight/day is faster and more evenly distributed in the drying method with Hybrid tools than direct drying (3) In red fruit, selective harvests tend to decrease more quickly in weight loss and water content until the second week, compared to red fruit rainbow harvest. (4) Selective harvested red fruit has the best physical quality and chemical content.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Berdasarkan pengujian yang telah dilakukan seluruh kopi greenbean tergolong ke dalam biji ukuran besar. Biji kopi yang baik dapat dilihat dari hasil pengukuran biji yaitu memiliki ukuran biji yang seragam sesuai dengan size masing-masing (Hidayat, Prasetyo, and Fahrurrozi 2021). Sebaran ukuran biji lebih banyak dipengaruhi oleh jenis varietas kopi yang digunakan daripada jenis pengolahannya (Yusianto and Widyotomo 2013).…”
Section: Uji Ukuran Bijiunclassified